An autopsy case of ovarian mucinous cystic tumor complicated by ovarian abscess and a review of the English literature. Issue 11 (16th November 2022) - Suzuki, Daisuke; Meguro, Shiori; Inagaki, Koji; Hashimoto, Masahiro; Kawasaki, Hideya; Kosugi, Isao; Enomoto, Yasunori; Sugiyama, Miho; Fukushima, Mayu; Iwashita, Toshihide
Abstract: Ovarian tumors are rarely associated with abscesses. Herein, an autopsy case of an ovarian mucinous cystic tumor complicated by an abscess, along with a review of previous cases, suggests the necessity of considering ovarian abscess as a cause of inflammation in patients with the ovarian tumors. Abstract : Cases of ovarian tumors complicated by abscesses are extremely rare and have not been reviewed previously. This autopsy case report, along with the literature review, is useful in raising awareness of ovarian tumors complicated by abscesses.